Tra società civile e autoritarismo cinese: la donna e le organizzazioni sociali tra legalità e illegalità - Graziani, Giulia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The aim of this essay is to try to extend the metaphor of the “out of place” to the Chinese civil society and to the women’s rights and feminist social organisations. Firstly, the “out of place” is what results from the attempted adoption of purely western theories, springing from western thought and culture; secondly, “out of place” is determined by the quest of interstitial space, where the social organisation can work in the blurred boundaries between legal and illegal. In the first part are analysed the different configurations of Chinese civil society determined by the lack of an accurate separation of the spatial border between State and civic space. In the second part are examined the role and the function of the women’s rights and feminist social organisations, which according to the degree of State subjugation the issues, the woman’s identity and the strategies of action will change.